Water Recycling System Through Filtration to Increase Production Efficiency at Small-Scaled Tofu Industry - Iwan Aang Soenandi; Florensa Rosani Purba; Ivan Tanra (Journal of Innovation and Community Engagement, 2022)
Tofu industry, which consider as a small and medium scale industry (UMKM), use a lot of water in its production process. In order to increase its profit, they need to increase the efficiency of clean water usage. One method is through recycling the wastage water into a clean water so it can be used in the production process. In order to recycle the wastage water, people make use of a passive filter to reduce the dissolved solid and acidity in wastage water so it can be similar with fresh water. From the results of our experiment, an average of 30 litres of recycled water can be used in the production process which reflect to increment efficiency of 5% per day in production process. Therefore, as an impact of the economy, this water recycling process will reduce the production cost of making tofu using of recycled water. And from the social aspect it affects the reduction of fresh water from the ground and reduce odours that will occur in environment.